A systematic review of deliberation research in marine and coastal case studies - Paramita, Adiska Octa; Partelow, Stefan; Fujitani, Marie (Frontiers in Marine Science, 2023)
Deliberation is an important concept in marine and coastal systems research because it is a key feature of many practical governance approaches such as participatory management, co-management, Integrated Coastal Zone Management, and Marine Spatial Planning. However, the research trends on deliberation have yet to be fully reviewed and evaluated to assess future opportunities and knowledge gaps in the field. In this article, we systematically review the literature to provide evidence on deliberation in marine and coastal governance systems. We review 187 case studies from peerreviewed articles worldwide, guided by three areas of inquiry: (1) how deliberation is applied to frame the problem of the case studies, (2) methodologies used to evaluate and design deliberation processes, and (3) recommendations to increase the effectiveness of deliberation processes. Findings indicate there is uneven spatial distribution of studies between the global north and the global south. Most case studies used deliberation to develop recommendations related to participatory governance and most of the researchers actively participated to solve real-world problems by creating a deliberation process. In addition to that, recommendations from case studies indicate deliberation processes can provide a framework to enhance participatory governance/management and science-policy integration. Finally, we discuss the implications of the findings to guide continued research and practice engaged with deliberation activities. Our systematic review provides a foundational baseline for understanding the research trends on deliberation in marine and coastal governance systems. The findings of this review are relevant for future researchers and practitioners who consider deliberation as an essential element of participatory approaches in natural resource governance, especially in marine and coastal sectors.